Depression in multiple sclerosis: effect of brain derived neurotrophic factor Val66Met polymorphism and disease perception. (12th January 2016) - Santoro, M.; Nociti, V.; De Fino, C.; Caprara, A.; Giordano, R.; Palomba, N.; Losavio, F.; Marra, C.; Patanella, A. K.; Mirabella, M.; Gainotti, G.; Quaranta, D.
Abstract : Background and purpose: Depression is common amongst subjects with multiple sclerosis (MS), and several investigations have explored different determinants of this condition, including physical disability, psychological and psychosocial factors. The brain derived neurotrophic factor (BDNF) Val66Met polymorphism has been associated with depression. The aim of this study was to analyze the influence of disease‐related factors, BDNF Val66Met polymorphism and perception of disease on the severity of depression in MS. Method: In total, 136 MS patients (88 women) were recruited and genotyped for BDNF rs6265 polymorphism at nucleotide 196 (G/A) using 'high resolution melting'. Depressive symptoms were assessed by the Multiple Sclerosis Depression Rating Scale. Perception of health status was assessed using the SF‐36 questionnaire. Results: A multivariable linear regression model showed that the best predictors of depression were the SF‐36 General health ( β = −0.209; P = 0.013), Mental health ( β = −0.410; P < 0.001) and Social activity ( β = −0.195; P = 0.035) scores; physical disability (assessed by the Extended Disability Status Scale score) was directly correlated to depression severity on univariate analysis, but it was not a relevant predictor of depression on multivariate analysis; other variables directly related to the disease (treatment, annual relapsing rate) and the BDNF Val66Met polymorphism were not significantly associated with depression. Conclusion: Perception of the health status is the principal predictor of depressive symptoms in our sample. This result supports the hypothesis that the subjective interpretation of the disease's consequences is one of the main factors in determining depression in MS.